Caffeine improves physical and cognitive performance during exhaustive exercise - Hogervorst, E.; Bandelow, S.; Schmitt, J.; Jentjens, R.; Oliveira, M.; Allgrove, J.; Carter, T.; Gleeson, M. (Medicine & Science in Sports & Exercise, 2008)
Caffeine is thought to act as a central stimulant and to have effects on physical, cognitive, and psychomotor functioning.